The violation of the National Minimum Wage Act in South Africa and recommendations for improving compliance - Nzama, Malusi (Department of Commercial Law, 2024)
South Africa is rated as one of the most unequal countries in the world, with the majority of its population living in abject poverty, or entirely dependent on one source of income for their livelihood. On top of the high unemployment rate, most workers who are employed or engage in some form of labour cannot afford basic living necessities such as food, transport, and health care. As a result, the government adopted the National Minimum Wage Act (NMWA). The Act aims to narrow the wage gap, reduce the pool of the working poor, and improve the material conditions of the worker's families. The broader objective of the Act is to observe the Constitution's mandate to social security, and its values of dignity. The Act protects workers against unfair remuneration by unprincipled employers. It builds upon the Basic Conditions of Employment Act of 1997, which enforces fair working conditions, including wages. The effectiveness of the Act, since its promulgation has, however been limited due to a high rate of violation and non-compliance amongst employers. The high rate of non-compliance has thrived despite of the existing enforcement systems and structures. The main challenges to non-compliance include insufficiency and undertraining of labour inspectors, lack of inspector resources, lack of public awareness of the legislation, tedious compliance procedures, lenient non-compliance penalties, labour migration trends, informalisation of labour and an increase of triangular forms of employment, including the gig economy. However, there is an observation that a sectoral approach yields to more noncompliance than an across board or blanket minimum wage. Nonetheless, it is important to consider whether the sectoral approach is more fitting for South Africa's economic circumstances. The prevailing non-compliance circumstances are not beyond remedy. There is evidence of countries that have been able to improve minimum wage enforcement, although they have had rife non-compliance. The Department of Employment and Labour can improve compliance through intensifying public awareness, reviewing enforcement procedures, reviewing inspection procedures, the formalisation of labour sectors, tightening non-compliance penalties, and mobilising trade unions and employers as party to national minimum wage compliance. This dissertation discusses the reasons for the violation of NMWA and proposes solutions and interventions that can be adopted by the Department of Employment and Labour (DoL) in improving compliance amongst South African employers.